Shrinkage behaviour of self-compacting concrete with higher binder content: experimental results and predictive equation - Yuvaraj Bhirud; Om Vaidya; Satish More; Ayub Shaikh; Amol Pawar; Lalit Pawar; Pradeep Yeole (Discover Materials)
Abstract The present study explores the potential benefits of increasing binder content in self-compacting concrete (SCC). Three concrete mixtures with varying binder content (550, 600, and 650 kg/m3) were investigated to evaluate their workability, compressive strength, and shrinkage. Findings indicate a significant enhancement in strength over the concrete's lifespan with higher binder content, accompanied by improved stability and cohesion. Additionally, the study examines the economic advantages of utilizing fly ash as a partial binder replacement, thereby reducing reliance on costly superplasticizers. However, existing prediction models for concrete shrinkage (IS 1343-2012, BS EN 1992-1-1-2004, and ACI 209 R-92) proved inadequate for high-binder SCC. To bridge this knowledge gap, a novel equation for predicting shrinkage in SCC with increased binder content was developed based on experimental data. This research contributes to the optimized design and cost-effective application of high-strength SCC in the construction industry.